Understanding gut-liver axis nitrogen metabolism in Fatty Liver Disease - Delgado, Teresa C.; de las Heras, Javier; Martínez-Chantar, María L. (Frontiers in Endocrinology, 2022)
The homeostasis of the most important nitrogen-containing intermediates, ammonia and glutamine, is a tightly regulated process in which the gut-liver axis plays a central role. Several studies revealed that nitrogen metabolism is altered in Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD), a consensus-driven novel nomenclature for Non-Alcoholic Fatty Liver Disease (NAFLD), the most common chronic liver disease worldwide. Both increased ammonia production by gut microbiota and decreased ammonia hepatic removal due to impaired hepatic urea cycle activity or disrupted glutamine synthetase activity may contribute to hepatic ammonia accumulation underlying steatosis, which can eventually progress to hyperammonemia in more advanced stages of steatohepatitis and overt liver fibrosis. Furthermore, our group recently showed that augmented hepatic ammoniagenesis via increased glutaminase activity and overexpression of the high activity glutaminase 1 isoenzyme occurs in Fatty Liver Disease. Overall, the improved knowledge of disrupted nitrogen metabolism and metabolic miscommunication between the gut and the liver suggests that the reestablishment of altered gut-liver axis nitrogenous balance is an appealing and attractive therapeutic approach to tackle Fatty Liver Disease, a growing and unmet health problem.